A Closer Look: How I Changed My Mind about Luther and the Reformation during the Last Decade - Rahner, Johanna (The sixteenth century journal, 2017)
The article discusses the impact that the Protestant Reformation, and 16th century German theologian Martin Luther's role in making the Reformation come about, had on the history of Germany, including on the Catholic Church. An overview of the Reformation's impact on German identity, including cultural identity, is provided.